Development of Impulse and Momentum Teaching Materials Using the Inquiry-Discovery Learning Model to Train Students' Creativity - Siti Rahmah; M Mastuang; Dewi Dewantara (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This research is motivated by the importance of creativity abilities based on the objectives of the 2013 Curriculum. Therefore, the purpose of this study is to describe the feasibility of impulse and momentum teaching materials using the inquiry-based discovery learning model to train students' creativity. This type of research is research and development with the ADDIE model. Data were obtained through an instrument validation sheet, a lesson plan implementation sheet, and THB. Data were analyzed descriptively qualitatively, averagely, and N-gain. The results showed: (1) teaching materials were valid because the validity of the lesson plans was 3.44; teaching materials of 3.46; LKPD of 3.45; and THB of 3.42 in the very valid category, (2) teaching materials including practical because the RPP component can be implemented in a very practical category, (3) teaching materials including effective because the N-gain value is 0.69 in the medium category. Thus, the teaching materials of the inquiry-discovery learning model that have been developed are feasible to train students' creativity and can be applied in physics learning.